Exosome encapsulated albumin nanoparticles target delivery of DBET6 as a treatment for triple-negative breast cancer - Han Yu; Jingyuan Zhao; Dan Wu; Hong Yuan (PLoS ONE, 2026)
Triple-negative breast cancer (TNBC) is a highly aggressive disease with significant mortality, and there is an urgent need for therapies that can effectively target the disease and enhance patient survival rates. The BET family protein BRD4 plays a key role in the development and progression of TNBC. Its degrader, dBET6—a proteolysis-targeting chimera (PROTAC) molecule—shows promising anti-tumor potential but suffers from low bioavailability and poor tissue selectivity. To improve its targeted delivery efficiency, this study developed a novel nanodrug delivery system, Exo-BSA@dBET6, which encapsulates dBET6 within bovine serum albumin (BSA) nanoparticles and further coats them with milk-derived exosomes, leveraging both the natural targeting ability of exosomes and the high drug-loading capacity of BSA. The results demonstrated that Exo-BSA@dBET6 has a uniform particle size of approximately 85.89 nm, good stability, high encapsulation efficiency, and excellent biocompatibility. In vitro experiments showed that this nanosystem significantly enhanced the cellular uptake of the drug in MDA-MB-231 cells, primarily through clathrin-mediated endocytosis, and exhibited efficient lysosomal escape. Compared to free dBET6 and BSA@dBET6, Exo-BSA@dBET6 displayed stronger cytotoxicity, significantly induced apoptosis, increased reactive oxygen species (ROS) levels, reduced mitochondrial membrane potential, and up-regulated caspase-3 protein expression. Western blot analysis further confirmed that Exo-BSA@dBET6 effectively degraded BRD4 protein, down-regulated c-Myc, and up-regulated Bax expression. Transcriptome sequencing analysis indicated that the nanosystem exerts anti-tumor effects by modulating key signaling pathways such as PI3K-Akt and Rap1. This study successfully constructed an exosome-modified albumin-based nanodrug delivery system that significantly enhances the targeting and anti-TNBC efficacy of dBET6, providing a new strategy for the targeted therapy of TNBC.